Stability of Non-enzymatic Glucose Sensor Based on Platinum Micro-/Nanostructures. (2015) - Urban, S.; Unmüssig, T.; Daubinger, P.; Kieninger, J.; Urban, G.
Abstract: Stability of hierarchical micro- and nanostructured platinum electrodes for non-enzymatic glucose sensors were investigated taking into account the two major aspects of stability. The first aspect, the loss of sensitivity due to poisoning by reaction products was significantly minimized by using a potential-step protocol during chronoamperometric and electrochemical impedance spectroscopy measurement, which led to a significant increase in sensor stability. In the second part the modification of the electrode surface during potential cycling operation due to rearrangement of the metal nano structures was investigated. It was shown that for the structured platinum layer a change in morphology together with a decrease of the roughness factor Rf can be observed.